Componentes bioactivos y valor nutricional de tres variedades de harina de quinua malteada (Chenopodium quinoa Willd.) - Aguilar Izquierdo, Julio César (2017)
The bioactive components and the nutritional value were determined in three varieties of milled quinoa flour (Chenopodium Quinoa Willd.): INIA Salcedo, red Pasankalla and black Collana. The malting was performed following the parameters: a time of 4 h and a water quantity of 1:1.5 in relation to grain: water in the imbibition stage; the germination at 25 °C for 3 days and the drying at 55 °C for 24 h. The quinoa´s characterization presents: the total phenolic content varied from 59.875 to 97.491 mg of acid gallic equivalents/ 100 g D.M., total flavonoids varied from 75.193 to 88.331 mg of quercetin equivalents/ 100 g D.M., antioxidant capacity a range from 17.484 to43.297 (Percent inhibition of DPPH radical) and a good quality respect to the proteins content (12.731-16.791 g/100 g D.M.). The malting resulted in an increase in bioactive compounds and antioxidant activity of the three varieties of quinoa flour, obtaining the highest value of total phenolic compounds (145.876 mg of acid gallic equivalents/ 100 g D.M.) and antioxidant capacity (58.103%) in red Pasankalla. In relation to the nutritional value, an increase of the content of total carbohydrates, reducing sugars, vitamin C and energy; and a decrease of the content of humidity, ash, fat and protein content in the three varieties of quinoa flour is reported, with the exception of the black Collana variety, which raised its protein value to 18.137 g/ 100 g m.s. The principal components analysis (PCA) showed that malting improves the bioactive potential and nutritional value in quinoa flour; pointing the INIA Salcedo by its great aptitude for malting by its increase of 3.51% and 45.05% of reducing sugars and total carbohydrates respectively, whereas the black Collana variety predominated by its protein content and the variety red Pasankalla had the highest bioactive potential. This research demonstrated that the three varieties of quinoa have an excellent potential to be malted by the positive effects in their bioactive compounds, as well as its nutritional profile emerging as a new alternative for an adequate nutrition.